Peningkatan Kualitas Pembelajaran Manajemen Sumber Daya Manusia Melalui Magang Perusahaan (Studi Kasus Pada Mahasiswa Manajemen Yang Sudah Mengikuti Praktik Magang Universitas Islam Malang) - Fahrezi, Muhammad Ilham; Pardiman, Pardiman; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the description and model of improving the quality of human resource management learning through company internships for management students at the economics and business faculty. Using the phenomonological method, this research focuses on descriptive research with a qualitative approach. There were 4 research informants determined by those who were directly involved in the activities to be researched. Data collection methods were carried out by interviews and documentation. The analysis flow uses an interactive analysis model with techniques used in the analysis including data collection, data reduction, data presentation and drawing conclusions. The results of the research show that overall it can be concluded that there are 3 divisions, namely for students, study programs and companies. For students: increasing work readiness and the importance of internship experience, developing professional competencies and honing skills, establishing professional networks. For study programs: collaboration with industry, improving the quality of graduates, the importance of assessment systems and achievements in internships. For companies: recruitment of potential talent, increasing productivity, building reputation and benefits for the company. Keywords: Quality Of Learning, Human Resource Management, Company Internships